Biofuels and the role of space in sustainable innovation journeys - Raman, Sujatha; Mohr, Alison (Elsevier, 2014)
This paper aims to identify the lessons that should be learnt from how biofuels have been envisioned from the aftermath of the oil shocks of the 1970s to the present,and how these visions compare with biofuel production networks emerging in the 2000s. Working at the interface of sustainable innovation journey research and geographical theories on the spatial unevenness of sustainability transition projects,we show how the biofuels controversy is linked to characteristics of globalised industrial agricultural systems. The legitimacy problems of biofuels cannot be addressed by sustainability indicators or new technologies alone since they arise from the spatial ordering of biofuel production. In the 1970-80s, promoters of bioenergy anticipated current concerns about food security implications but envisioned bioenergy production to be territorially embedded at national or local scales where these issues would be managed. Where the territorial and scalar vision was breached, it was to imagine poorer countries exporting higher-value biofuel to the North rather than the raw material as in the controversial global biomass commodity chains of today. However, controversy now extends to the global impacts of national biofuel systems on food security and greenhouse gas emissions, and to their local impacts becoming more widely known. South/South and North/North trade conflicts are also emerging as are questions over biodegradable wastes and agricultural residues as global commodities. As assumptions of a food-versus-fuel conflict have come to be challenged, legitimacy questions over global agri-business and trade are spotlighted even further. In this context, visions of biofuel development that address these broader issues might be promising. These include large-scale biomass-for-fuel models in Europe that would transform global trade rules to allow small farmers in the global South to compete, and smallscale biofuel systems developed to address local energy needs in the South.